1996
DOI: 10.1097/00004647-199607000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Metyrapone, an Inhibitor of Glucocorticoid Production, Reduces Brain Injury Induced by Focal and Global Ischemia and Seizures

Abstract: Increasing evidence indicates that glucocorticoids (GCs), produced in response to physical/emotional stressors, can exacerbate brain damage resulting from cerebral ischemia and severe seizure activity. However, much of the supporting evidence has come from studies employing nonphysiological paradigms in which adrenalectomized rats were compared with those exposed to constant GC concentrations in the upper physiological range. Cerebral ischemia and seizures can induce considerable GC secretion. We now present d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 59 publications
5
74
2
1
Order By: Relevance
“…Our data corroborate clinical studies in which poststroke cortisol concentrations were predictive of stroke outcome (10)(11)(12). Furthermore, experimental manipulations that increase blood corticosterone concentrations during or after cerebral ischemia increase infarct volume in rats (13), whereas manipulations that decrease corticosterone concentrations are neuroprotective (14,15). Thus, in both humans and rodents, elevated Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data corroborate clinical studies in which poststroke cortisol concentrations were predictive of stroke outcome (10)(11)(12). Furthermore, experimental manipulations that increase blood corticosterone concentrations during or after cerebral ischemia increase infarct volume in rats (13), whereas manipulations that decrease corticosterone concentrations are neuroprotective (14,15). Thus, in both humans and rodents, elevated Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In humans, post-stroke cortisol concentrations are predictive of stroke outcome; high cortisol is associated with increased morbidity and mortality (10)(11)(12). Furthermore, experimental manipulations in rats that increase blood corticosterone concentrations during or after cerebral ischemia also increase infarct volume (13), whereas surgical or pharmacological suppression of corticosterone concentrations is neuroprotective (14,15). It has been proposed that rather than killing neurons directly, exposure to high concentrations of corticosteroids typically induces a physiological state that renders neurons more susceptible to subsequent neurologic insults (16).…”
mentioning
confidence: 99%
“…Intraischemic treatment of rats with metyrapone, a drug that attenuates stress-induced corticosterone production during MCAO, reduces infarction volume in the cortex and striatum by approximately 50%. 21 In contrast, treatment with exogenous corticosterone daily, beginning at reperfusion, results in increased infarction volume in hippocampus, neocortex, and striatum after global cerebral ischemia. 19,22 Taken together, these studies suggest that there is a potentially wide temporal window during which elevated serum glucocorticoid concentrations can affect ischemia-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of circulating stress hormone levels confirms the role of stress in recovery from stroke. Pre-treatment with the corticosteroid synthesis inhibitor metyrapone acts neuro-protectively when given after MCAO in rats (Smith-Swintosky et al, 1997;Krugers et al, 1998Krugers et al, , 2000. In contrast, Risedal et al (1999) found that pre-lesion treatment with metyrapone did not influence infarct size, while post-lesion administration exacerbated infarct volume and motor deficits in rats.…”
Section: Introductionmentioning
confidence: 98%